2018
DOI: 10.18203/2320-6012.ijrms20181764
|View full text |Cite
|
Sign up to set email alerts
|

Gender based perspectives about organ donation among students in a medical school in North India

Abstract: Background: Deaths due to organ failure are reaching alarming numbers mainly due to paucity of organ donation. The medical students who are the future doctors hold promise to alleviate this paucity by willing to register as a donor themselves as well as facilitating cadaver organ donation process. Objective was to assess the perspectives (awareness and attitudes) of medical students regarding organ donation.Methods: The present cross sectional descriptive study was conducted among 280 undergraduates’ students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“… 49 64 68 69 75 86–89 A qualitative study from an urban area in the southern region of India also found brain death as a new concept for many and hard to accept among the public. 90 Also, many were not aware about the organ donor card, 67 83 88 91–94 where and how to register and obtain an organ donor card 40 50 53 55 56 70 71 94 95 —an important component for organ donor registration. In addition, knowledge on the law that governs organ donation was also found to be low.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 49 64 68 69 75 86–89 A qualitative study from an urban area in the southern region of India also found brain death as a new concept for many and hard to accept among the public. 90 Also, many were not aware about the organ donor card, 67 83 88 91–94 where and how to register and obtain an organ donor card 40 50 53 55 56 70 71 94 95 —an important component for organ donor registration. In addition, knowledge on the law that governs organ donation was also found to be low.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, knowledge on the law that governs organ donation was also found to be low. 40 71 92 96 97 Though a study among Indians living in UK showed that disinterest, emotional distaste, family opposition and religion to be the underlying cause for reluctance to register, 58 among Indians living in India, the awareness on brain death, organ donor card, where and how to register were reported as important factors along with family and religion among individuals who were willing to register. 40 49 50 53 55 64 67 69–72 86 91–96 98 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation